2004
DOI: 10.1080/02841860410029357
|View full text |Cite
|
Sign up to set email alerts
|

Proxy ratings of patient quality of life Factors related to patient–proxy agreement

Abstract: It is generally agreed that patients are the best raters of their quality of life (QL). Where it is not possible to obtain information from the patient the use of proxies can be an alternative. The proxy can be a significant other or a healthcare provider. The use of a proxy offers a solution to non-response. The accuracy of proxy reports is most typically determined by examining the extent to which patient and proxy ratings agree. A literature overview shows that agreement depends on several factors. Methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 31 publications
(28 reference statements)
7
64
3
1
Order By: Relevance
“…This may suggest that there is not a difference in predicting additional care, whether it is for an individual or for a proxy such as a parent. This conclusion is consistent with previous research that found proxy ratings to be reasonably accurate and to have significant implications for the type of care and treatment provided (Essen, 2004). In addition, Bigatti et al (2007) found moderate overall agreement on quality of well-being between patient and proxy ratings of women with fibromyalgia.…”
Section: Discussionsupporting
confidence: 80%
“…This may suggest that there is not a difference in predicting additional care, whether it is for an individual or for a proxy such as a parent. This conclusion is consistent with previous research that found proxy ratings to be reasonably accurate and to have significant implications for the type of care and treatment provided (Essen, 2004). In addition, Bigatti et al (2007) found moderate overall agreement on quality of well-being between patient and proxy ratings of women with fibromyalgia.…”
Section: Discussionsupporting
confidence: 80%
“…49 Other studies have found better agreement for concrete objective symptoms that require less interpretation. 20,[50][51][52][53] Reporting of fatigue, a 'subjective' symptom, 25,54 in the medical records was extremely low (8%), suggesting that clinicians are less likely to recognise or document this symptom. Symptoms which required subjective assessment by parents or clinicians in younger children were reported infrequently, and their high negative agreements reflected the high concordance regarding the absence of those symptoms.…”
Section: Interpretation Of Findings In Relation To Previously Publishmentioning
confidence: 99%
“…Caregivers and health care providers are considered main candidates for the role of proxy. There are contradictory findings about QoL assessments by physicians: some studies show good patient-physician agreement (9,14,17), while others do not (3,18). On the other hand, caregivers such as a partners, parents or children may provide a more valid evaluation of the patient's QoL since they have a longer and closer contact with, and more understanding of, the patient (8,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the patient is the main source of QoL assessments (3,8,9). However, there are situations in which the patient is not able or does not want to properly respond to the QoL questions.…”
Section: Introductionmentioning
confidence: 99%